Novel experimental modelling of the hydrodynamic interactions of arrays of wave energy converters. (December 2017) - Nader, Jean-Roch; Fleming, Alan; Macfarlane, Gregor; Penesis, Irene; Manasseh, Richard
Highlights: A novel approach for experimental modelling of WEC arrays interactions is presented. The q-factor for two heaving and surging generic WECs is derived. Constructive and destructive interactions were found. The Stereo videogrammetry technique was adapted to measure the wave field. Abstract: Wave energy converters (WECs) range significantly in respect of concepts, technologies and design maturation, with the majority of devices at an early commercial stage. To date, most large scale deployments have been conducted with a single WEC. However, there is a necessity to expand these to 'arrays' or 'farms' in the future in order to reduce both installation and maintenance cost per unit as well as harnessing maximum energy at a given site. There are complex hydrodynamic and environmental implications which require consideration when moving from a single device installation to an array of devices. Many theoretical and numerical studies exist in this domain, however, limited experimental investigations have been performed due to the cost and size related to testing facilities as well as the complexity of the experiment and related instrumentation. This paper presents a novel experimental approach, performed as part of a larger project, aiming to address a critical knowledge gap: understanding the performance of WEC arrays, and to develop a methodology to accurately model an array of WECs. The experimental investigation utilised Australia's most technically advanced wave basin at the Australian Maritime College, specialist institute of the University of Tasmania. For the first time, it applied the phenomenological theory to experimental hydrodynamic investigation of array of generic WECs by separating the problem into its diffraction and radiation problems. Such approach removes the need of power-take-off modelling and control. Using a post-processing analytical model, the q -factor, the parameter representative of the array performance, for several configurations can be derived. Furthermore a bespoke stereo-videogrammetry method was developed to measure the wave field around and in the lee of the array. This paper describes the hydrodynamic approach and experimental methods developed as part of this project and presents preliminary results related to array q -factor and wave field measurements.